(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
the article reveals the history of the turkic khaganate in central asia rolan, for the reasons of its conquests, the hephtalite processes of the conquest of the state, the form of government, including the invasion of the arab caliphate. The study of the history of the Turkish Khaganate occupies an important place in the history of our country. Its significance is primarily determined by the successful struggle against the Turkish Khaganate of the invasion of the sasanian state. Created and saved our people from the domination of turkic spirituality is an external threat conditions for its further progress. Long live the people in the region who have not the dog its name to the palace, whose spirituality, language, and traditions are the same. At present, it is a scientific idea that form its young people to the server spirituality the spirituality of our national amo an integrated part of the turkic people